Protocol for the establishment of the Pediatric Registry for Stroke as a Multidisciplinary Approach to healthcare research (PRiSMA) study - Lucia Gerstl; Victoria Lieftüchter; Eva Jung; Florian Heinen; Dewi Bakker; Steffen Berweck; Mark Dzietko; Thomas Liebig; Martin Olivieri; Rainer Seidl; Ronald Sträter; Clara Haacke; et al. (PLoS ONE, 2026)
Background Childhood stroke is a rare but potentially life-threatening event that can occur at any age. It requires prompt diagnosis and appropriate treatment, and, in view of the frequent neurological and neurocognitive sequelae, long-term care in a multidisciplinary and multiprofessional setting. The management of stroke in children, which differs in many aspects from stroke in adults, often relies on local expert opinions and retrospectively collected data rather than high-quality evidence from prospective randomized controlled clinical trials, especially in the acute phase. Aims The Pediatric Registry for Stroke as a Multidisciplinary Approach to healthcare research (PRiSMA) study aims to systematically collect longitudinal prospective observational data across the acute and long-term phases to optimise diagnosis, personalised acute therapy, neurorehabilitation, and prevention of recurrent stroke. The data will inform development of further hypothesis-driven studies of childhood stroke in national and international networks. Furthermore, PRiSMA will facilitate case-specific collaboration within the registry network, allowing treating clinicians to consult experienced colleagues on complex cases. Methods In PRiSMA all children and adolescents (>28 days of life, ≤ 18years) with arterial ischemic stroke (AIS) or hemorrhagic stroke (HS) are eligible for recruitment. The nationwide multicenter, systematic data collection is performed in the acute and chronic phases, extracted from patient medical records supplemented by direct registry-specific medical history provided by caregivers. In addition, a questionnaire-based data on quality of life and behaviour will be collected. International collaborations are established across Germany, Austria and the Netherlands. Status Currently, 16 centres in Germany and 1 centre in Austria have commenced recruitment. 30 patients are currently (17 Nov 25) enrolled after arterial ischaemic stroke and 1 after haemorrhagic stroke.